Indledning: Antropologiske forståelser af aldring - Grønbæk Jensen, Stine Grønbæk Jensen; Steno, Anne Mia; Teglgaard Christensen, Loa Kristine; Hillersdal, Line; Grünenberg, Kristina; Rasmussen, Jon Dag; Schwennesen, Nete; Segal, Lotte Buch; Ryborg Jønsson , Alexandra Brandt (Tidsskriftet Antropologi, 2023)
Indledning til Tidsskriftet Antropologi #86 Aldring